2019
DOI: 10.2220/biomedres.40.125
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cognitive functions by oral intake of <i>Hericium</i><i> erinaceus </i>

Abstract: Hericium erinaceus has been recognized as medical mushroom since ancient time, but its scientific evidence for human health has been still uncertain. In this study, we tested a randomized, double-blind, placebo-controlled parallel-group comparative study to evaluate the improvement of the cognitive functions by taking supplements containing fruiting body of H. erinaceus for 12 weeks. We performed three kinds of tests: Mini Mental State Examination (MMSE), Benton visual retention test, and Standard verbal paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 40 publications
0
24
0
1
Order By: Relevance
“…In another randomized, double-blind placebo-controlled study, administration of 0.5 g H. erinaceus fruiting body in cookies over 4 weeks showed a reduction in anxiety and depression in menopausal women (n = 30) compared to those taking placebo, as measured by the Center for Epidemiologic Studies Depression Scale and Indefinite Complaints Index (Nagano et al, 2010). In the third randomized, double-blind, placebo-controlled parallelgroup comparative study, the consumption of cookies containing 0.8 g of H. erinaceus fruiting body dry powder alleviated the deterioration of short memories and improved the cognitive functions in 31 participants with an average age of 61.3 years old over the period of 12 weeks, as measured by MMSE (Saitsu et al, 2019). Prior studies have reported that NGF could enhance neurogenesis-inducing effects, which led to antidepressant and antianxiety activities (Shohayeb et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In another randomized, double-blind placebo-controlled study, administration of 0.5 g H. erinaceus fruiting body in cookies over 4 weeks showed a reduction in anxiety and depression in menopausal women (n = 30) compared to those taking placebo, as measured by the Center for Epidemiologic Studies Depression Scale and Indefinite Complaints Index (Nagano et al, 2010). In the third randomized, double-blind, placebo-controlled parallelgroup comparative study, the consumption of cookies containing 0.8 g of H. erinaceus fruiting body dry powder alleviated the deterioration of short memories and improved the cognitive functions in 31 participants with an average age of 61.3 years old over the period of 12 weeks, as measured by MMSE (Saitsu et al, 2019). Prior studies have reported that NGF could enhance neurogenesis-inducing effects, which led to antidepressant and antianxiety activities (Shohayeb et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other dietary supplements that have shown significant improvements on different cognitive domains are fungi and algae extracts (Hericiumerinaceus, Tremella fuciformis and Laminaria japonica), other plant extracts (Eleutherococcussenticosus leaf, Drynariafortuneirhizome, combined sage, rosemary and melissa, auraptene, astaxanthin and matured hop bitter acids), minerals such as magnesium, medium-chain triglycerides and the complex Twendee X (supplement containing a mix of eight antioxidants). The consumption of the above antioxidant and anti-inflammatory supplements not only significantly improved subjective memory complaints [84] and scores in different cognitive domains such as psychomotor and processing speed [73], working memory [76,77,79,81], short-term memory [74,76,77,84], spatial working memory [75,79,81,87], verbal episodic memory [78], verbal fluency [75,82,83], language [75,79,81,87], executive functions [79,82,84] and attention [79,83,87], but also cortical gray matter integrity in AD-related brain regions [84]. The spermidine-rich plant extract also had an impact on memory performance in subjects with SCD, although this was not significant, probably due to the small sample size (n = 30) and/or the short follow-up period (3 months) [85].…”
Section: Other Types Of Dietary Supplementsmentioning
confidence: 99%
“…A 12-week parallel intervention study in 31 cognitively healthy adults allocated to consume either a combination of an extract of Eleutherococcussenticosus (ES) and rhizomes of Drynariafortunei (DR) (203.01 mg/d of ES leaf extract, and 20.01 mg/d of DR), showed significant improvements in language, semantic fluency and figure recall scores [75]. Consumption of Hericiumerinaceus supplement (3.2 g/d) for 12 weeks also improved cognitive function and prevented cognitive decline in a study of 34 cognitively healthy subjects over the age of 50 years [76]. The effect of fermented Laminaria japonica was also evaluated in 60 moderately active senior subjects randomized to consume either 1.5 g/d of this supplement or a sucrose pill as placebo.…”
Section: Other Types Of Dietary Supplements (N = 15)mentioning
confidence: 99%
“…Moreover, confirm the safety of H.erinaceous and could be used in dementia prevention. 5 Another recent Italian study in 2019 on mice reported that two-month of oral intake of H.erinaceous reversed the decline of age and restore cognition memory, which means this mushroom could have neurogenesis effect. 6 In line with a vitro study conducted in Malaysia showed that Lion's Mane mushrooms contain neurotrophic factors (hericenones and erinacines) which might induce nerve growth factors essential for the maintenance of optimum neural body structure to operate.…”
Section: The Role Of Lion's Mane Mushroom In Cognitive Functionmentioning
confidence: 99%